UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MENGGUNAKAN MODEL PROJECT BASED LEARNING PADA SISWA SEKOLAH DASAR - Annisa Nurul Aflah; Rizki Ananda; Yenni Fitra Surya; Ory Syafari Jamel Sutiyan (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
This research is motivated by the low results of creative thinking skills in students in class V SD TI 030 Batu Belah, Kampar District. One solution to overcome this problem is to apply the Project Based Learning model. The purpose of this study was to describe the increase in creative thinking skills using the Project Based Learning Model for students in class V SD TI 030 Batu Belah. This research strategy is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, and reflection. The subjects of this study were 25 grade V students, 14 male students and 11 female students. Data collection techniques in the form of documentation, observation, and tests. Based on the results of data analysis, it can be seen that by using the Project Based Learning (PjBL) model, it can be seen that the value of the creative thinking ability of fifth grade students at SD TI 030 Batu Belah in the second cycle of action has increased when compared to the value in the first cycle. the second cycle of the first meeting, namely 72% increased at the second meeting to 88%. So it can be concluded that the application of the Project Based Learning learning model can improve creative thinking skills in students in class V SD TI 030 Batu Belah Kampar District.